„Ponadczasowość” piśmiennictwa retorycznego - Bering, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The main aim of this article is to compare some selected rhetorical treaties from Antiquity, Middle Ages and Early Modern. It is striking that in the rhetorical works from different epochs the same formulas are used and the topic remains identical. This analysis can be a strong argument for the timeless nature of rhetoric.